Evaluation of Cytotoxic Potential of Ethanolic and Acetone Extract of Abelmoschus moschatus on Hep G2 Cell Lines - Sebastian, Rani; Venkatachalam, Gomathi; D, Umamaheswari; M, Sakthi Abirami; BS, Venkateswarlu (Asian Journal of Biological and Life Sciences)
This study aims to highlight the cytotoxic effects of Abelmoschus moschatus on Hep G2 cell lines by methylthiazoltetrazolium (MTT)-cleavage assay. The yellow tetrazolium salt MTT is converted by mitochondrial dehydrogenases of metabolically active cells to an insoluble purple formazan product, which was then solubilized with dimethylsulfoxide. The optical density of this homogeneous solution was suitable for a precise spectrophotometric measurement by a plate reader at a wavelength of 570 nm. The cytotoxic effect of acetone extract was shown at 92.01 μg/ml and ethanol extract was shown at 72.16 μg/ml respectively when compared with the standard Doxorubicin. The results showed that both the extracts posess significant cytotoxic activity. The studies reveal that natural plant extract has the ability to work as a defense by enhancing the immune system against cancer.
Keywords: Abelmoschus moschatus; Anticancer activity; cytotoxicity; Hep G2 cell lines; IC50; MTT assay